The Effect of Training on Employee Performance in Healthcare: Does Behavioral Competence Matter? - Lilik Lestari (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: Behavioral competencies have been recognized as key to organizational success in achieving their goals. Understanding how to improve them can help identify factors that determine the achievement of strategic plans. However, research on training mechanisms that contribute to the performance of healthcare employees is still limited. Using the Human Capital Theory framework, this study aims to examine the influence of training on behavioral competencies and its effects on employee performance. Research Method: This study employed a quantitative approach, using primary data collected through questionnaires distributed to 85 employees at Dr. Ario Wirawan Lung Hospital. The data were analyzed using Partial Least Squares Structural Equation Modeling. Results and Discussion: The results revealed that training positively influenced behavioral competencies but had no significant effect on employee performance. Further findings indicate that behavioral competencies positively impact employee performance in healthcare. Implications: The study's findings encourage hospital management to improve employees' core competencies and behaviors through various training programs. Originality: This study provides empirical evidence about the role of training, behavioral competencies, and employee performance in enhancing healthcare performance.